Kedudukan Hukum Akta Kelahiran Anak di luar Kawin yang Dicantumkan Nama Ayah - Rosida Amaliasari (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
Extramarital child is always causing complex problem, whether positive law as well as Islamic law. Several problems are among others: First, the legal status of birth certificate of the extramarital child that includes and does not include the name of the father. Second, related to the status of the extramarital child as heir by the inclusion of the name of the father in the birth certificate whether based on positive law as well as Islamic law. By virtue of decision Number 46/PUU-VIII/2010 the Constitutional Court has provided a decision that guarantees the fulfillment of civil rights for the extramarital child. With the fulfillment of civil rights, it is expected to be able to provide justice for the extramarital child, however, such matter covers the overall aspects or not including the extramarital child that has been recognized as legal child by including the name of the father in the birth certificate is entitled to become a heir as the right of legal child and proven with Deed of Authenticity. Moreover the problem arising whether in Islamic law such matter is also becoming a legal matter and entitled to become a heir.